2020
DOI: 10.1111/ahg.12379
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of the ethnic Lao groups from mainland Southeast Asia revealed by forensic microsatellites

Abstract: Purpose Laotians and Lao Isan are widely spread Lao groups who live in Laos and northeastern Thailand, respectively. We explored the genetic structure between them and other ethnic groups from Thailand to clarify historical patterns of admixture between Tai‐Kadai and Austroasiatic speakers, and to expand the forensic reference database for the region. Subjects and Methods We combined new genetic data for 554 individuals from 12 populations, typed for 15 autosomal short tandem repeats, with available data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…This population structure and history remains largely unexplored by genetic studies, which have almost exclusively analyzed autosomal short tandem repeat (STR) loci, and mitochondrial DNA (mtDNA) and male specific Y chromosome (MSY) sequences. These studies revealed the relative genetic heterogeneity of the AA groups and homogeneity of TK groups (Kampuansai et al, 2017(Kampuansai et al, , 2020Kutanan et al, 2014Kutanan et al, , 2017Kutanan et al, , 2019Srithawong et al, 2015Srithawong et al, , 2020 and contrasting male and female genetic histories in the region, especially for the matrilocal vs. patrilocal hill tribes (Oota et al, 2001;Kutanan et al, 2018aKutanan et al, , 2019Kutanan et al, , 2020. While genome-wide data provide much richer insights into population structure and genetic history, previous genome-wide studies of Thai/Lao populations are either primarily from northern populations (HUGO Pan-Asian SNP Consortium, 2009;Xu et al, 2010;Lipson et al, 2018) or do not provide any information on ethnolinguistic background (Wangkumhang et al, 2013;Lazaridis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This population structure and history remains largely unexplored by genetic studies, which have almost exclusively analyzed autosomal short tandem repeat (STR) loci, and mitochondrial DNA (mtDNA) and male specific Y chromosome (MSY) sequences. These studies revealed the relative genetic heterogeneity of the AA groups and homogeneity of TK groups (Kampuansai et al, 2017(Kampuansai et al, , 2020Kutanan et al, 2014Kutanan et al, , 2017Kutanan et al, , 2019Srithawong et al, 2015Srithawong et al, , 2020 and contrasting male and female genetic histories in the region, especially for the matrilocal vs. patrilocal hill tribes (Oota et al, 2001;Kutanan et al, 2018aKutanan et al, , 2019Kutanan et al, , 2020. While genome-wide data provide much richer insights into population structure and genetic history, previous genome-wide studies of Thai/Lao populations are either primarily from northern populations (HUGO Pan-Asian SNP Consortium, 2009;Xu et al, 2010;Lipson et al, 2018) or do not provide any information on ethnolinguistic background (Wangkumhang et al, 2013;Lazaridis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several studies of TK groups from Thailand revealed a genetic relationship with ANs (Kutanan et al, 2017, 2018), suggesting a shared ancestry of TKs and ANs in continental Asia predating the migration of ANs to Taiwan and the Pacific islands ~5 kya (Kutanan et al, 2018; Wei et al, 2017). The beginning of TK speaking groups' separate migrations into MSEA dates approximately 2–2.5 kya (Liu et al, 2020), these groups then expanded and dominated in Thailand and Laos from around 1 kya (Kampuansai et al, 2017; Kutanan et al, 2018; Srithawong et al, 2020). Our STRUCTURE analysis using modern population data supported these results, showing little of the connection between the TKs in MSEA and ANs in Taiwan but a much more similar structure between the TK, AA, and ST populations in Vietnam (Kinh), Laos (Laotian), northern Thailand (Tai, Lao Isan, Lue, Mon, Khmer, and Bru) and southern China (Li, Han, and Yi) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…They assimilated to the indigenous populations both culturally and genetically, from agricultural techniques and linguistic terms to genetic exchanges (Kampuansai et al, 2017;Kutanan et al, 2017;Li et al, 2016). The history of these migrations and establishment of TK speaking populations was supported by genetic evidence from China (Li et al, 2016;Sun et al, 2013), Thailand (Kampuansai et al, 2017;Kutanan et al, 2017;Srithawong et al, 2015), and Laos (Kutanan et al, 2017;Srithawong et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Genomic DNA was extracted using the Gentra Puregene Buccal Cell Kit (Qiagen, Hilden, Germany) according to the manufacturer’s instructions. An additional 412 genomic DNA samples from other Laotian and Lao Isan populations were retrieved from previous studies ( Kutanan et al, 2017 ; Srithawong et al, 2020 ; Kutanan et al, 2021 ) ( Table 1 ). Ethical approval for this study was provided by Khon Kaen University for Lao Isan and Naresuan University for Laotian.…”
Section: Methodsmentioning
confidence: 99%
“…Several previous genetic studies of Laotian and Lao Isan were based on mitochondrial (mt) DNA and Y chromosome ( Bodner et al, 2011 ; Kutanan et al, 2014 ; Kutanan et al, 2017 ; Kutanan et al, 2019 ; Kutanan et al, 2021 ) and genome-wide data ( McColl et al, 2018 ; Tätte et al, 2019 ; Kutanan et al, 2021 ). However, data from forensic microsatellites or short tandem repeats (STRs) has been much less published, especially with populations from Laos ( Srithawong et al, 2015 , 2020 ). Furthermore, previous STRs data were based on 15 autosomal loci.…”
Section: Introductionmentioning
confidence: 99%